2021
DOI: 10.3390/medicina57101091
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Sonographic Evaluation of Cesarean Section Scar Niche in Pregnancy: A Prospective Longitudinal Study

Abstract: Background and Objectives: To investigate the prevalence of a Cesarean section (CS) scar niche during pregnancy, assessed by transvaginal ultrasound imaging, and to relate scar measurements, demographic and obstetric variables to the niche evolution and final pregnancy outcome. Materials and Methods: In this prospective observational study, we used transvaginal sonography to examine the uterine scars of 122 women at 11+0–13+6, 18+0–20+6 and 32+0–35+6 weeks of gestation. A scar was defined as visible on pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…For second-trimester assessment of niche length, depth, width and RMT, the interobserver 95% LOA were all ≤ 4.0 mm, which is comparable to our interobserver reproducibility for offline 2D still images. Similar to our study, both Naji et al and, more recently, Savukyne et al reported CS scar detection rates of 88.8% and 77.9%, respectively, during pregnancy, with excellent agreement for CS scar and niche visibility 13,14 . Zimmer et al demonstrated that the ability to visualize the CS scar was significantly greater with increasing cervical dilatation at the time of CS 24 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For second-trimester assessment of niche length, depth, width and RMT, the interobserver 95% LOA were all ≤ 4.0 mm, which is comparable to our interobserver reproducibility for offline 2D still images. Similar to our study, both Naji et al and, more recently, Savukyne et al reported CS scar detection rates of 88.8% and 77.9%, respectively, during pregnancy, with excellent agreement for CS scar and niche visibility 13,14 . Zimmer et al demonstrated that the ability to visualize the CS scar was significantly greater with increasing cervical dilatation at the time of CS 24 .…”
Section: Discussionsupporting
confidence: 92%
“…and, more recently, Savukyne et al . reported CS scar detection rates of 88.8% and 77.9%, respectively, during pregnancy, with excellent agreement for CS scar and niche visibility 13,14 . Zimmer et al .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Still, there is no known potential role of the ultrasound assessment of myometrial thickness in managing patients after cesarean delivery. We have previously shown a good inter- and intra-observer agreement for measurements of CS scar niche, RMT, and LUS thickness in all three trimesters of pregnancy [ 16 ]. More extensive and good quality studies are indicated to examine the uterine scar myometrial thickness ratio between trimesters or cut-off values for use in clinical practice, and to incorporate these measurements in deciding the mode of delivery or predict complications.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the examination of uterine diverticulum mainly includes ordinary transabdominal and transvaginal two-dimensional color Doppler ultrasound, three-dimensional transvaginal ultrasound (TVUS), hysterography (SHG), magnetic resonance imaging (MRI), and hysteroscopy [ 17 ]. Uterine contrast-enhanced ultrasonography can well observe the existence of scarred diverticulum, but it cannot measure the size of the diverticulum, and some people are allergic to contrast agents.…”
Section: Introductionmentioning
confidence: 99%